Implikasi Jarh wa al-Ta’dil terhadap Keautentikan Hadits (Studi Validitas Dalil Qunut Subuh Madzhab Al-Syafi’i) - Rohim, Abdul; Arifin, Tajul (Asian Journal of Islamic Studies and Da'wah, 2024)
This study examines the influence of the science of jarh wa ta'dil in determining the validity of qunut hadith for every subuh prayer in the Shafi'i school of thought. This study investigates how Shafi'i scholars apply the science of jarh wa ta'dil to assess the validity and authenticity of hadith and provide recommendations for Muslims in responding to qunut subuh hadith. This study uses a qualitative method with a descriptive-analytic approach. Data is collected from relevant books, scientific journals, and online articles. Data analysis is carried out using content analysis methods. The results of the author's research find that the science of Jarh wa ta'dil plays a very important role for Shafi'i scholars in particular and generally for all scholars of madhhab in assessing the credibility of a sanad matan, such as analyzing the behavior of hadith narrators, piety, honesty, even more specifically such as from the quality of the narrator's memorization, and the author found that the hadiths that were used as arguments for qunut subuh by the Shafi'i madhhab could be used as hujjah, Based on the results of the study, it is concluded that a hadith nash can be used as the basis for a religious law when it is at the level of maqbul hadith, at least hasan ligoiri, and for qunut hadith in the Shafi'i school of thought it is classified as maqbul hadith so it can be used as evidence for its implementation.